Cataloging for school librarians - Kelsey, Marie Ellen 1948- (Rowman & Littlefield, 2018)
"The theory and practice of cataloging and classification for students and practitioners who need a clear sequential process to help them overcome cataloging anxiety"--Provided by publisher.